Vision Nursing and Dental Health, Department of Radiology and Emergency Medicine and Health administration, sociology and other medical specialties and their role in infection control and prevention - Mutared Mana sherfan Alyami, Hadi Salem Hamad ALsuliman, Yahya Hames Yahya Al-Abbas, Hadi Naji Nasser Al Yami, ALI RUBAYYI S ALYAMI, SAMI GHAREEB SALEM ALANAZI, Mohammed Salem Manea Al-Thanyh, Yahya Hussain Ali Majrashi; Manea Mohammed Al Mutarid, MESFER FARIS MOHAMAD AL QIRAD, Salih Faris Muhamad Alqarad, Mesfer Naji Hamad Alyami, MOHAMMED YAHYA SAEED ALYAMI, MAHDI YAHYA SAEED ALYAMI, Fawzi Mubarak Saad ALkhadem (Journal of International Crisis and Risk Communication Research, 2024)
Infection control and prevention are vital constituents of international healthcare systems, directing to decrease the liability of infectious diseases and increase patient results. This review discovers the role of multidisciplinary health professionals in infection control, concentrating on understandings fromEmergency Medicine, nursing, dentistry, dental hygiene, Radiology, health administration, sociology, and epidemiology. Each discipline adds unique expertise to prevent and achieve infections in clinical and community settings. Nurses act as forefront providers, applying hygiene practices and educating patients to moderate hospital-acquired infections. Dentists and dental hygienists prevent oral infections that can lead to systemic complications, highlighting sterilization and patient education. Health managers confirm effective policy implementation, resource distribution, and submission observing. Sociologists address behavioral and societal factors influencing infection risks, promoting equitable access to healthcare and tailored public health interventions. Epidemiologists analyze infection patterns, assess risks, and provide evidence-based recommendations for preventive measures. By adding efforts from these disciplines, healthcare systems can progress comprehensive strategies to address infection-related challenges. However, challenges such as resource constraints, inconsistent protocols, and communication gaps must be addressed. Future innovations in technology, training, and interdisciplinary collaboration will further enhance infection control efforts.